If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6x + 9 = x + -6 + 15 Reorder the terms: 9 + 2x + -6x = x + -6 + 15 Combine like terms: 2x + -6x = -4x 9 + -4x = x + -6 + 15 Reorder the terms: 9 + -4x = -6 + 15 + x Combine like terms: -6 + 15 = 9 9 + -4x = 9 + x Add '-9' to each side of the equation. 9 + -9 + -4x = 9 + -9 + x Combine like terms: 9 + -9 = 0 0 + -4x = 9 + -9 + x -4x = 9 + -9 + x Combine like terms: 9 + -9 = 0 -4x = 0 + x -4x = x Solving -4x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -4x + -1x = x + -1x Combine like terms: -4x + -1x = -5x -5x = x + -1x Combine like terms: x + -1x = 0 -5x = 0 Divide each side by '-5'. x = 0 Simplifying x = 0
| (7x^2+5x)/(x^2+1)-5x/(x^2-6) | | 5w+2.7=12 | | 9x^2+169=0 | | 3x+9x-4=3(4x+9) | | -8=-(-6x-3) | | .5x-4=0 | | 2y+2(y-6)=8y-6(y-10) | | 9(x-1)=-126 | | 7/36*x=5 | | 4(x-2)=2x-2 | | 52=p-41 | | -(8x-4)-(3x-5)+10=-9(x-1)-(5x+8+3) | | 7x-2+5=10x+4 | | p+13=-10 | | 6x+9-5x=16 | | -2(3x-6)+5=-1 | | 8y=5y+9 | | Rx+Sy=Tfory | | (-5+7i)+(-8-9i)=0 | | (x)=3x+4 | | x-9/5-1=x-3/4 | | 5x-11=4x+6 | | 4w-6w=12 | | 9x-15=6x | | X-3/4(2x-12)=7x/2+5 | | 7x-12-4x=5x-7 | | f(x)=3x+36 | | 27/8(29/6k+1/4)=-4149/32 | | 56x^2-23x=63 | | (7/w-4)=(-5/(2w-8))+4 | | 3x+y+x+y= | | (x-8)-(6x+4)= |